Community attachment: perceptions of context matter. Issue 1 (1st January 2021) - Ma, Guizhen
ABSTRACT: Social bonds have been a focus in understanding community attachment. Community context is also critical to fostering community attachment. While community context assessed by objective measures such as population size and density has been linked to community attachment, the effects of both objective context and subjective context measured by individuals' perceptions of community context on attachment to urban communities have not been well understood. Combining the survey data for 26 metropolitan and micropolitan communities in the US. from 2008 to 2010 with the Census Bureau's data, this study examines how individual characteristics, social bonds, subjective and objective measures of community context affect sentimental attachment to the communities. The results show that positive perceptions of community social and physical environments significantly encourage community attachment, and their effects are stronger than those of objective context measures and social bonds. These findings suggest that community attachment is not necessarily weakened in urban areas.